Retirement and Growing Old: Which Model of Protection? - Bernard Delhausse; Sergio Perelman; Pierre Pestieau (Luxembourg Income Study (LIS), 1994)
This paper focuses on the effect ageing has on intragenerational equity in seven LIS countries. Using current distribution schemes as baselines, the authors compare the projected effects of four benefit scenarios on aged inequality.
Keywords: 330